2020
DOI: 10.1186/s12877-020-01908-x
|View full text |Cite
|
Sign up to set email alerts
|

‘I wanted to talk about it, but I couldn’t’, an H70 focus group study about experiencing depression in early late life

Abstract: Background Knowledge about experiences of depression among younger-old adults from the general population is limited. The aim was to explore experiences of depression in early late life. Methods Sixteen participants in the population-based Gothenburg H70 Birth Cohort Studies (12 women and 4 men) who had reported a history of depression between ages 60–70 took part in focus group discussions (n = 4). Data were analyzed using focus group methodology.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 55 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…The prevalence is reported to be almost twice as high among women compared to men, but little is really known about the role of gender expression in relation to depression epidemiology, and whether the prevalence of late-life depression may change over time. Recent findings revealed that adults between 60 and 70 years old want to talk about their experiences of depressions to increase their health literacy regarding possible preventive measures, available treatment options, and pharmaceutical side effects (145).…”
Section: Anxiety and Depressionmentioning
confidence: 99%
“…The prevalence is reported to be almost twice as high among women compared to men, but little is really known about the role of gender expression in relation to depression epidemiology, and whether the prevalence of late-life depression may change over time. Recent findings revealed that adults between 60 and 70 years old want to talk about their experiences of depressions to increase their health literacy regarding possible preventive measures, available treatment options, and pharmaceutical side effects (145).…”
Section: Anxiety and Depressionmentioning
confidence: 99%
“…Male individuals tend to struggle with masculine stereotypes concerning a perceived need to be in control, successful, self-reliant, and not to show signs of weakness 18,52,92,93 : "I think you grow up with itmen don't cry… it's the social group that does it… 'don't be a sissy'" 94 . They often experience more difficulty expressing their emotional feelings and thoughts about their depressive disorder 41,95 : "You have to be as macho as possible… perhaps makes it hard to express your feelings verbally" 92 .…”
Section: Experiencing Depression Across Gendersmentioning
confidence: 99%
“…Due to these inconsistent findings, it is important to seek more nuanced information regarding the interplay of diet and depression, which may be achieved by exploring individuals' experiences with food and mood. Experiences of depression and depressive symptoms have been extensively reported within qualitative contexts [12][13][14], yet individual perceptions of food and its relationship to mood remain largely unexplored.…”
Section: Introductionmentioning
confidence: 99%